2007
DOI: 10.1677/jme.1.02164
|View full text |Cite
|
Sign up to set email alerts
|

Identification and subcellular localization of the Na+/H+ exchanger and a novel related protein in the endocrine pancreas and adrenal medulla

Abstract: C exchangers (NHE) constitute a family of membrane antiporters that contribute to the regulation of cellular pH and volume in many tissues, including pancreatic islets. We investigated the molecular identity of NHE in rodent and human endocrine pancreas, and determined its cellular and subcellular localization. NHE1 was the most abundantly expressed isoform in rat islets, and was also expressed in mouse and human islets. By western blot, an antiserum raised against the C-terminus end of NHE1 confirmed the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…We confirm (35) that the corresponding mRNA is absent from their islets and show that no significant compensatory expression of another isoform occurred. Our observations that DMA had no effect on pH c in islets from Under basal conditions (3 mM glucose), the lack of NHE1 did not affect islet pH c in HCO 3 Ϫ medium but resulted in a marked lowering of pH c in HEPES medium.…”
Section: Nhe1 and Islet Cell Ph C Regulation-nasupporting
confidence: 80%
See 2 more Smart Citations
“…We confirm (35) that the corresponding mRNA is absent from their islets and show that no significant compensatory expression of another isoform occurred. Our observations that DMA had no effect on pH c in islets from Under basal conditions (3 mM glucose), the lack of NHE1 did not affect islet pH c in HCO 3 Ϫ medium but resulted in a marked lowering of pH c in HEPES medium.…”
Section: Nhe1 and Islet Cell Ph C Regulation-nasupporting
confidence: 80%
“…NHE1 (encoded by Slc9A1) was the most expressed among the isoforms associated with the plasma membrane (NHE1-NHE5 and NHE10). Using radioactive RT-PCR, we recently showed that NHE1 is strongly expressed, whereas NHE2 and NHE5 are weakly expressed, and NHE3 and NHE4 are not detected in rat islets (35).…”
Section: Nhe1 and Islet Cell Ph C Regulation-namentioning
confidence: 99%
See 1 more Smart Citation
“…[28]; ChIP sequencing data available on the Human Genome Browser; and section II.7 for further information on regulation of NHE1 expression). Although a few studies have reported NHE1 splice variants in rodent and human tissues [31][32][33], a single variant seems to be the only or by far the predominant form of NHE1 in most tissues.…”
Section: The Na + /H + -Exchanger Isoform 1 Nhe1 (Slc9a1) Ii1 Tmentioning
confidence: 99%
“…These findings suggested unspecific, NHE1-independent effects of EIPA and DMA in islets, possibly involving KEY POINTS inhibition of another amiloride-sensitive NHE or direct inhibition of K ATP channels [22,23]. In addition to full-length plasmalemmal NHE1, b cells were found to express a shorter splice variant of NHE1 that localizes specifically to insulincontaining LDCVs [7]. Although full-length NHE1 protein ($100 kDa) was absent from islets in NHE1 swe/swe mutant mice, the shorter splice variant ($65 kDa) was still present.…”
Section: Role Of Sodium/hydrogen Exchanger 1 In B Cellsmentioning
confidence: 98%